Utilisation of Durum Grains for Producing Wheat Grits for Dalia Preparation: Durum Wheat Grits for Dalia - Anuj Kumar,; Sharma, Manthn; Verma, Pooja; Kumar, Sunil; Pandey, Vanita; Kumar, Dinesh; Gupta, OP; Singh, Vijay; Singh, Charan; Sharma, Amit Kumar (Journal of Cereal Research, 2025)
Wheat grits are considered to be broken/ cut/ chopped/ cracked wheat pieces, which are consumed after cooking. In the present study, wheat grits obtained from three durum wheat varieties (DDW 47, DDW 48 and DDW 55) using chakki were evaluated for physicochemical and sensorial attributes. The colour values in terms of Hunter colour attributes (L, a, b) for grits obtained varied from 59.7-62.8, 4.7-6.8, and 19.7-24.7, respectively. Further, the yellow pigment content of wheat grits varied from 5.53 to 6.65 ppm. Grits also contained 9.12-10.4% protein and 1.33-1.43% mineral content. Wheat grits manufacturing via milling also contributed towards the generation of by-product, containing about 10.98-11.01% protein and 2.13-2.42% ash content, which has the potential to fulfil dietary needs via appropriate value addition. Further, the cooked sweetened milk-based dalia was liked by the sensory panellists, both as hot and cold desserts, with overall acceptability scores of 7.00-7.17 and 7.33-7.42, respectively. Durum-based wheat grits can be utilised as a mode to encourage value addition and product diversification.